Cultivating New Post-secular Political SpaceGuest Edited by Roger Haydon Mitchell. Issue 4 (2nd October 2018) - Mitchell,
Abstract : ABSTRACT The emergence of post-secular new political space is increasingly recognised as both urgent challenge and beckoning opportunity for innovative political intervention. The concept is framed around three defining characteristics. Firstly, it refers to socio-economic space vacated by government and demarcated by extremes of poverty and marginalisation requiring mitigation by charities, faith communities and the like. Secondly, it is evidenced in local contexts by an obvious lack of social mobility and blatant discrepancies in income, educational outcomes and life expectancy. Thirdly, it is ontological space. Arguably for the first time in a generation, the deep political structures are accessible to recognition and transformation. Fourthly, it is European space exemplified by the increasing challenge to the post-war European project and the burgeoning nationalism and xenophobia exacerbated at least in part by the influx of refugees, asylum seekers and economic migrants. This special issue of Global Discourse assembles six articles and responses emanating from a desire to cultivate and not colonise this emerging space for overall well-being.